The elements of journalism : - Kovach, Bill (Three Rivers Press, 2007)
The elements of journalism are: Journalism’s first obligation is to the truth; Its first loyalty is to citizens; Its essence is a discipline of verification; Its practitioners must maintain an independence from those they cover; It must serve as an independent monitor of power; It must provide a forum for public criticism and compromise; It must strive to make the significant interesting and relevant; It must keep the news comprehensive and proportional; Its practitioners must be allowed to exercise their personal conscience.